Gestión municipal en la implementación de los servicios básicos y la calidad de vida de los pobladores del distrito de Belén - Maynas, 2020 - Vela Rodríguez, Watson Haroldo (2022)
The general objective of this research was to determine the relationship between municipal management in the implementation of basic services and the quality of life of the inhabitants of the district of Belén - Maynas, 2020. Determining itself as a descriptive and correlational research, design non-experimental, work that has taken a sample of 333 citizens, who were surveyed to evaluate the corresponding variables, collecting data through the questionnaire. The work concludes that the municipal management in the implementation of basic services maintains a deficient behavior, this due to the fact that the residents observed deficiencies such as the inadequate supply of water to all homes, the authorities do not comply with the projects within the established period caused the development of the community, likewise, the basic services implemented are not satisfactory for the entire community. Likewise, the quality of life of the inhabitants has a bad behavior, because there have been deficiencies in the education, electricity, water and drainage services because they are not accessible to all the inhabitants since their economy is not enough to solve cats and provide for their family, in addition, the authorities rarely prioritize projects that improve the environment and the environment in the community. In general, a relationship of 0.881 was calculated, which is high positive, therefore, it is determined that the relationship is significant between municipal management in the implementation of basic services and the quality of life of the inhabitants, contrasted by a significance of 0.000.